Peran Dan Wewenang Syahbandar Dalam Penegakan Standar Kelaiklautan Kapal Menurut Undang-Undang (UU) Nomor 66 Tahun 2024 Tentang Perubahan Ketiga Atas Undang-Undang Nomor 17 Tahun 2008 Tentang Pelayaran: Efektivitas Pengawasan Dan Penindakan - Gunawan Widjaja; Wagiman Wagiman; Wibowo Laksono Widodo (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study discusses the role and authority of the Harbourmaster (Syahbandar) in enforcing ship seaworthiness standards based on Law Number 66 of 2024 concerning the Third Amendment to Law Number 17 of 2008 on Shipping. This research employs a normative juridical method with statutory and conceptual approaches. The results indicate that the Harbourmaster holds a strategic function as a port official with full authority to ensure that ships meet technical, administrative, and operational requirements before departure. The effectiveness of supervision is reflected in the implementation of strict seaworthiness inspection procedures and the issuance of Sailing Approval Letters (Surat Persetujuan Berlayar or SPB) only for seaworthy ships. Furthermore, the Harbourmaster’s enforcement mechanism against violations of ship seaworthiness is carried out administratively and involves law enforcement agencies for serious violations. According to Soerjono Soekanto’s theory of law enforcement, the Harbourmaster’s supervision falls under the preventive stage to avert violations, while enforcement constitutes the repressive stage as an effort to create a deterrent effect and ensure legal compliance in the shipping sector.